The Central Business District: A Study in Methodology - Aiken, Robert Samuel (My University, 1967)
This thesis provides a critical appraisal of those techniques, which have been employed in studying the functional characteristics of the C.B.D.; from this basis, a number of techniques are amalgamated, and employed in conjunction, in an effort to provide a better and more comprehensive methodology in the study and understanding of the ensemble of functions found in the Central Business District. A conceptual framework is set by a review of the pertinent literature, and a chapter on the author's own concept of the C.B.D. The approach is essentially interdisciplinary.
Keywords: Geography; Geography